Feeding Habits of the Common Solea , Solea Vulgaris (Quensel, 1806) from Benghazi Coast, Mediterranean Sea, Libya - El-Mor, Mohammad El-Sayed (Al-Mukhtar Journal of Sciences, 2008)
A total of 550 specimens of Solea vulgaris were collected from monthly catches by trawling net operating on the Benghazi coast on the Mediterranean Sea from January to December 2007. The annual diet composition, monthly variations in the diet composition and the variations of the diet with the length and the intensity of feeding were studied. Solea vulgaris feed on a wide variety of prey types, polychaetes, copepods, algae, seagrasses, mollusks and amphipods with frequent quantities of sediments. Polychaetes and copepods were the major food items all year round. Polychaetes and copepods were found in all length groups of Solea vulgaris, they decreased as the size increased, whereas seagrasses and algae increased as the size increased.The diet composition of Solea vulgaris is indicative of a generalist feeding strategy. The feeding activities were quite high during spring and autumn seasons.